Hubungan Pengetahuan Ibu Tentang Gizi Balita, Asupan Energi Dan Protein Balita Dengan Status Gizi Balita Di Wilayah Kerja Puskesmas Banyudono I Kabupaten Boyolali - Setiono, Beni, Setyaningrum Rahmawaty, A., M.Kes., Ph.D, Susi Dyah Puspowati, M.Si (2016)
Background: Nutritional status of children is influenced by many factors, including mother's knowledge about nutrition and intake nutrition of children. Objective: The purpose of this study was to determine the relationship of mother's knowledge about healthy food, energy and protein intake of children and nutritional status of children at Puskesmas Banyudono I, Boyolali. Methods: A cross-sectional approach was done in 53 mother's and her child to collect data about mother's knowledge on healthy food, energi, protein intake and anthropometric of her child using a questionaire about healty food, food frequency questionnaire over a last month and z-score (weigh/age) respectively. Results: The results showed that 28 (52.8%) mother's are knowledgeable about nutrition with medium category, 24 (45.3%) infants had normal energy intake, 20 (50.9%) infants had a protein intake above their need. Most toddlers have a good nutritional status with a percentage of 83.0%, 15.1% children are malnutrition and 1,9% children are severe malnutrition. There is no relation between mother knowledge on healty food and the nutritional status of children (p=0.951), as well as energy intake and nutritionali status of children (p = 0.553) and protein intake and nutritionali status of children (p = 0.950).